“Flowers of Fathers:” Resistance and consolation in a catholic manuscript compilation, Bodleian MSS. Eng. th. b. 1–2 - McKeogh, K (University of Pennsylvania Press, 2022)
This essay reintroduces to scholars Bodleian MSS. Eng. th. b. 1–2, a substantial and enigmatic two-volume manuscript work bearing witness to the English Catholic community, its identity, its preoccupations, and the ways in which these found expression. The essay makes new arguments for the circumstances of the work's compilation and gives an account of its contents in order to facilitate further research into this important source. The manuscript's compiler sought to console and to educate his readership in the traditions and doctrines of the Catholic faith, but he also wrote to stir them to resistance against persecution. A rich example of lay authorship, the manuscript served as a vehicle for views that could not be expressed publicly, and it spoke for a community that identified itself as persecuted.